The open studio essays on art and aesthetics - Stewart, Susan 1952- (Chicago The University of Chicago Press, 2005)
"Susan Stewart is professor of English at Princeton University and a former MacArthur Fellow"--Jacket.
To take a chance -- On the art of the future -- Thomas Schutte : in Medias Res -- Hans-Peter Feldmann -- William Kentridge -- Armando Reveron : paintings and objects -- Tacita Dean -- The Eidos in the hand -- What thought is like : the sea and the sky -- Garden Agon : Ian Hamilton Finlay's Little Sparta, 1993-97 -- An after as before -- Framing abstraction -- On the threshold of the visible -- Organic form and perfection in painting -- Egg and dart : notes on the work of Anne and Patrick Poirier -- Death and life, in that order, in the works of Charles Willson Peale -- Explosion at San Giovanni in Laterano, summer 1993 : notes for Francis Bacon's Figure with meat -- Musical box -- Ann Hamilton -- At the Freud show : aide memoire.
Includes bibliographical references (pages 259-285) and index.
Keywords: Art; Aesthetics